The Effect of Using Digital Comics on Science Learning Outcomes of Grade VI SDN 1 Japurabakti - Rizkiyah, Rizkiyah; Nurkholis, Nurkholis; Setiana, Diana (LPPM Institut Pendidikan Nusantara Global, 2025)
This study aims to determine the effect of digital comic-based learning models on science learning outcomes. This research uses Quantitative, quasi-experimental methods with a research design of nonequivalent control group design. The population in this study were grade VI students of SDN 1 Japurabakti in 2024/2025. The sample used was 38 students from class VI SDN 1 Japurabakti. The research instrument used an essay test consisting of 10 questions about students' understanding of science lessons and a student response questionnaire consisting of interesting aspects, aspects of convenience and aspects of achieving learning objectives. Data processing techniques using normality test, homogeneity test, paired sample t-test, independent sample t-test and N-Gain test. The results showed that the application of digital comic media based on WEBTOON applications with the theme of earth friend comics implemented learning with 2 class groups, namely experimental classes and control classes. The experimental class that applied digital comic media with the results of student responses amounted to 89.5% with a very positive category. While the results of student tests show an increase in student science learning outcomes with the average pretest and posttest scores of the experimental class from 50.2 to 67.7 with an N-Gain of 0.22 including in the medium category. While based on the results of the science lesson understanding test, students experienced an increase in each indicator with a pretest average value of 50.5 and a posttest average value of 74.2 with a moderate category. The results showed that there was an effect of the digital Comics learning model on the science learning outcomes of students.